2020
DOI: 10.1111/php.13254
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Sirtuins in Skin and Skin Cancers

Abstract: Mammalian sirtuins (SIRTs 1‐7) are a family of NAD+‐dependent deacetylases with distinct subcellular localization and biological functions that regulate various important cellular processes. Among these, SIRTs ‐3, ‐4 and ‐5 are located in the mitochondria and have been implicated in caloric restriction, oxidative stress, aging and various human diseases. Emerging evidence has found dysregulation of mitochondrial sirtuins in multiple dermatological conditions, including responses to ultraviolet radiation (UVR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 93 publications
0
13
0
Order By: Relevance
“…SIRT3 also plays a key role in the regulation of several cellular processes, including transcription, insulin secretion, and programmed cell death (30). The ability of SIRT3 to regulate numerous cellular processes that are critical in cancer cell proliferation suggests it as a valid therapeutic target in the management of cancers, including cutaneous neoplasm (28,31). A study from our laboratory demonstrated that SIRT3 is overexpressed in human melanoma tissues and cell lines.…”
Section: The Sirtuins Sirt1 and Sirt3 And Their Downstream Targets Imentioning
confidence: 96%
See 1 more Smart Citation
“…SIRT3 also plays a key role in the regulation of several cellular processes, including transcription, insulin secretion, and programmed cell death (30). The ability of SIRT3 to regulate numerous cellular processes that are critical in cancer cell proliferation suggests it as a valid therapeutic target in the management of cancers, including cutaneous neoplasm (28,31). A study from our laboratory demonstrated that SIRT3 is overexpressed in human melanoma tissues and cell lines.…”
Section: The Sirtuins Sirt1 and Sirt3 And Their Downstream Targets Imentioning
confidence: 96%
“…Similarly, the mitochondrial sirtuin SIRT3 also appears to be involved in melanoma progression. Based on numerous studies, SIRT3 has emerged as a metabolic regulator, and its potential role in cancer is being intensively investigated (1,3,28). SIRT3 is known to affect most of the mitochondrial dynamics, including nutrient oxidation, generation of ATP, and detoxification of reactive oxygen species (ROS) (29).…”
Section: The Sirtuins Sirt1 and Sirt3 And Their Downstream Targets Imentioning
confidence: 99%
“…During aging, skin undergoes a complex plethora of biochemical and structural changes. For example, the role of NAD + -dependent deacetylases, known as sirtuins (SIRT 1–7), is fundamental to comprehend skin aging, particularly for photoaging, and the involvement of mitochondria biology (Su et al 2020 ). Sirtuins 3 (SIRT3), 4 (SIRT4) and 5 (SIRT5), which are localized in mitochondria, are implicated in aging, besides to oxidative stress response and caloric restrictions (Gambini et al 2011 ).…”
Section: -Lactate Ros and Mitochondria: Role In Skin Agingmentioning
confidence: 99%
“…It also plays important roles in the regulation of a variety of cellular processes, including transcription, insulin secretion, apoptosis and redox signaling (6). SIRT3 has also been implicated in multiple cutaneous functions including skin renewal, and response to environmental stressors (7,8).…”
Section: Introductionmentioning
confidence: 99%